Analisis Tingkat Literasi Keuangan Mahasiswa Program Studi Pendidikan Ekonomi - Anna Marganingsih; Emilia Dewiwati Pelipa (Jurnal Ekonomi dan Bisnis Digital, 2022)
The study aims to describe the level of Financial Literacy for students of the STKIP Persada Khatulistiwa Economic Education Study Program. This study uses a quantitative approach in the form of a survey. The number of respondents in this study a population of 72 people. The data collection technique used is indirect communication using a questionnaire instrument. Data analysis was processed using descriptive analysis. The results of the research show that the Financial Literacy Level of Students of the Economic Education Study Program at STKIP Persada Khatulistiwa is 66.28%. It can be concluded that the level of financial literacy of students of the Economic Education Study Program at STKIP Persada Khatulistiwa is in the medium category. This means financial literacy which includes; Knowledge and Ability to apply finance, Financial Attitude, and Financial Behavior still need to be improved.